Analysis of Flood Peaks Using The Mean Annual Flood Method - Hidayat, Acep; Basysyar, Basysyar; Rief Alkhaly, Yulius; Bin Ali, Md Nadir (International Journal of Engineering, Science and Information Technology, 2022)
The Kedang Pahu river is one of the tributaries of the Mahakam river. The research plan is located in Damai District, West Kutai Regency, East Kalimantan province. Recently, the Damai District and Damai Seberang areas have flooded activities that have caused the surrounding settlements to flood into residential areas and block existing road access. Planning analysis and knowing the annual flood elevation is essential. The analysis uses the method of calculating the mean annual flood (MAF) to search for the average annual flood discharge data and the search for the average annual elevation. Data validation using a simple linear regression method produces a correlation coefficient of 58.67%, or R-value = 0.5867. The analysis results in the value of Q1 or the 1st year period, the mean annual flood rate of the average annual flood discharge is 2576.0695 m³/second and the value associated with the magnifying factor (GF) is the average annual flood discharge rate of Q5=3014,00 m³/ sec, Q10 = 3529.22 m³/sec, Q20 = 4095.95 m/sec, Q50 = 5049.10 m³/sec, Q100 = 5847.68 m³/sec, Q200 = 6852.34 m³/sec, Q500 = 8423.75 m³/sec Q1000 = 9917.87 m³/sec. The analysis results at HEC-RAS 5.07 based on manning analysis showed the elevation values were Q1=18.47m, Q5=18.85m, Q10=18.86m, Q20=19.18m, Q50=19.74m Q100=19.99m. Researchers only show elevations up to Q100 or the 100th year because of limited data and the reviewed data accuracy.